Lewis Acid Catalyzed Regioselective Substitution of 2-Indolylmethanols with Pyrroles - Gao, Jun-Nan; Tan, Wen-Xin; Yang, Shuang; Wang, Ning-Yi; Han, Jiebin; Wang, Da-Hua; Zhang, Yu-Chen; Shi, Feng (Synthesis, 2025)
A Lewis acid catalyzed regioselective C2′-electrophilic substitution of 2-indolylmethanols with pyrroles has been established, which affords indole-based tetraarylmethanes in overall high yields (up to 99%) with excellent regioselectivities. Moreover, such indole-based tetraarylmethanes exhibit potent cytotoxicity against HepG2 cancer cells, which demonstrates their potential applications in medicinal chemistry. This reaction not only represents the regioselective C2′-electrophilic substitution of 2-indolylmethanols with aryl nucleophiles (Ar-Nu), but also provides a new strategy for the synthesis of biologically important tetraarylmethanes.
Keywords: indolylmethanols; pyrroles; electrophilic substitution; Lewis acids; tetraarylmethanes; regioselectivity